An Olefinic 1, 2‐Boryl‐Migration Enabled by Radical Addition: Construction of gem‐Bis(boryl)alkanes. (27th May 2019) - Zhao, Binlin; Li, Zexian; Wu, Yixiao; Wang, Yandong; Qian, Jiasheng; Yuan, Yu; Shi, Zhuangzhi
Abstract: A series of in situ formed alkenyl diboronate complexes from alkenyl Grignard reagents (commercially available or prepared from alkenyl bromides and Mg) with B2 Pin2 (bis(pinacolato)diboron) react with diverse alkyl halides by a Ru photocatalyst to give various gem‐bis(boryl)alkanes. Alkyl radicals add efficiently to the alkenyl diboronate complexes, and the adduct radical anions undergo radical‐polar crossover, specifically, a 1, 2‐boryl‐anion shift from boron to the α‐carbon sp 2 center. This transformation shows good functional‐group compatibility and can serve as a powerful synthetic tool for late‐stage functionalization in complex compounds. Measurements of the quantum yield reveal that a radical‐chain mechanism is operative in which the alkenyl diboronates acts as reductive quencher for the excited state of the photocatalyst. Abstract : Bor lässt Milde walten : Ein mildes katalytisches System für die Synthese von gem ‐Bis(boryl)alkanen über eine olefinische 1, 2‐Borylwanderung wurde entwickelt. Diese Methode ist gut verträglich mit funktionellen Gruppen und kann ein leistungsstarkes Hilfsmittel für die Funktionalisierung komplexer Verbindungen im späten Synthesestadium sein.